1978
DOI: 10.1007/bf02911894
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reactions involved in the deep‐fat frying of foods: VIII. Characterization of nonvolatile decomposition products of triolein

Abstract: A laboratory apparatus that could be used to treat pure triglycerides under simulated deep fat frying conditions was designed and built. By the use of this apparatus, the volatile decomposition products produced during frying could be quantitatively collected at the same time. Pure trilinolein was treated in this apparatus at 185 C for 74 hr. The volatile decomposition products were collected quantitatively'. Their fractionation and identification will be reported in a subsequent paper. The nonvolatile decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…They may also be involved in promoting carbon-carbon radical reactions via H-abstraction: Early researchers studied polymeric products of monoand polyunsaturated compound oxidation; their findings were summarized by Swern et al (85) and Gardner (86). By thermally oxidizing triolein under simulated deep-fat frying conditions, Paulose and Chang (87) showed that polymers were formed by both carbon-to-carbon and carbonto-oxygen linkages. Although they did not identify the precise form of the oxygen linkages, they found indications of the presence of ether linkages.…”
Section: Initiationmentioning
confidence: 99%
“…They may also be involved in promoting carbon-carbon radical reactions via H-abstraction: Early researchers studied polymeric products of monoand polyunsaturated compound oxidation; their findings were summarized by Swern et al (85) and Gardner (86). By thermally oxidizing triolein under simulated deep-fat frying conditions, Paulose and Chang (87) showed that polymers were formed by both carbon-to-carbon and carbonto-oxygen linkages. Although they did not identify the precise form of the oxygen linkages, they found indications of the presence of ether linkages.…”
Section: Initiationmentioning
confidence: 99%
“…According to Doi and Urakami (1 976), soybean oil used continuously for frying contained dioxoacids, epoxides, oxolans and pyrans. Polymers produced under frying conditions are bound mainly by carbon-carbon or ether bonds (Paulose and Chang 1978), but rarely by peroxide linkages (Pokorny 1989).…”
Section: Fryingmentioning
confidence: 99%
“…Owing to the complexity of the vegetable oil mixture of oxidation products, model frying or heating oil systems of a single triglyceride such as triolein and trilinolein have been studied to obtain a simpler mixture of oxidation products or potential volatile precursors (9)(10)(11)(12)(13)(14)(15)(16). One objective of this work with triolein and trilinolein was to better understand the production of negative odors in modified composition oils such as high-oleic-containing oils.…”
mentioning
confidence: 99%